Incidence of Natal Teeth in Sarlahi District of Nepal - Agrawal, Nitin Kumar; Khatry, Subarna K; LeClerq, Steven C; Katz, Joanne; Mullany, Luke C (Journal of Nepal Health Research Council, 2019)
Background: The presence of natal or neonatal teeth, which have been associated with environmental factors and hereditary syndromes, can have an impact on the psychosocial growth of children. Methods: We aimed to estimate the incidence of natal tooth in Sarlahi district of Nepal.Live births from Sarlahi district in Nepal were assessed for natal teeth and other related factors.Results: Among 28,695 live births between 2010 and 2017, we observed 7 cases of natal teeth accounting for an incidence rate of 2.44 per 10,000 (95% CI: 0.98 – 5.03). Out of 7 neonates with natal tooth, 4 were female and 3 were low birth weight (<2500 grams). None were preterm or had any associated cleft lip or palate.Conclusions: Incidence of natal tooth in Nepal is rare.It is important for health care providers to know about the possibility of occurrence of natal tooth and its management.Keywords: Incidence of natal tooth; natal tooth; neonatal tooth; Nepal.